MORPHOLOGICAL STRUCTURE OF NEUROEPITHELIAL CELLS IN RABBIT LUNGS (Journal of Science-Innovative Research in Uzbekistan, 2024)
The morphofunctional features of NET in the developing respiratory lung have been studied. Lungs of 23 rabbits aged 1-30 days served as a material for the study. Paraffin sections were stained with hematoxylin and eosin, according to the Van-Gizon method, impregnated according to the Grimelius method. Histochemical detection of acetylcholinesterase (AChE) activity was carried out on frozen sections of unfixed lungs by the method of M. Karnovsky and Roots. The study allowed to establish that in the rabbit lung NET cells are detected in the respiratory section. NET cells are located at the bronchiolo-alveolar junction, as well as within the alveolar sacs. NET cells range in size from small to quite large. NET cells have AChE activity. The location of NET cells at the bronchioloalveolar junction and the presence of AChE in their cells suggest their important role in the processes of growth and differentiation of pulmonary acinus structures.